Efficacy of Propranolol Combined with Different Modalities of Unilateral Adrenalectomy in a Case Series of 4 ARMC5-mutated Patients - Yu, Fan; Yu, Baowen; Zhou, Hongwen; Wei, He; Fan, Hong-Qi (Experimental and Clinical Endocrinology & Diabetes, 2025)
Limited research has explored the efficacy of β-blockers in combination with unilateral total, subtotal, or partial adrenalectomy in ARMC5-mutated patients with primary bilateral macronodular adrenocortical hyperplasia (PBMAH). Additionally, there is no consensus on determining the optimal side for adrenal gland resection. To assess the clinical utility of three unilateral adrenalectomy (ULA) modalities—total, subtotal, and partial—combined with β-blocker treatment in patients with PBMAH and Cushing’s syndrome (CS). This study was conducted at a single tertiary referral center involving a series of four patients with suspected CS. Diagnosis of PBMAH was confirmed through dexamethasone suppression testing, evaluation of ectopic receptor expression, and whole-exome sequencing. Three patients underwent unilateral total, subtotal, or partial adrenalectomy, respectively, while one patient declined surgery. All patients received β-blocker treatment. The median treatment duration among the four ARMC5-mutuated PBMAH patients was 30.5 months (range: 6–45 months). Two patients who underwent total or subtotal adrenalectomy on the side with more pronounced nodularity showed postoperative improvement in clinical CS signs, glycemic control, and hypertension. These two patients, along with another patient with bilateral diffuse (non-nodular) adrenal hyperplasia who declined surgery, showed further improvement in hypercortisolism and cortisol/adrenocorticotropic hormone (ACTH) ratio (CAR: plasma cortisol (nmol/L)/plasma ACTH (pg/ml), newly reported as a reliable parameter of cortisol secretory capacity in patients with adrenal CS) after propranolol treatment. The patient who underwent partial adrenalectomy on the side with less pronounced nodularity showed no significant improvement in hypercortisolism or CAR, and the response to propranolol was also unsatisfactory. All four cases harbored pathogenic variants in the ARMC gene, including two novel germline mutations.In ARMC5-mutuated patients with PBMAH, unilateral total adrenalectomy on the side with more pronounced nodularity appears to be an effective treatment option. Propranolol may be considered as an alternative or adjunctive therapy to ULA for managing hypercortisolism in those with ARMC5 mutations.
Keywords: β-blocker; Cushing’s syndrome; PBMAH; Unilateral adrenalectomy; ARMC5